Smart Parking System using Microsoft Azure - Leong, Weng Kit (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study will develop a mobile application using Android Studio that acts a front end for the user and using Microsoft Azure to support the backend operation. The main purpose of mobile application is to enable the user to pay the street parking under Majlis Bandaraya Kuching Selatan (MBKS) and Dewan Bandaraya Kuching Utara (DBKU) in Sarawak. Instead of ordinary parking payment application, the mobile application will ease the parking user by eliminating the issue caused by parking coupon.